Pengembangan Handout Berbasis Penelitian Uji Daya Antibakteri Ekstrak Daun dan Kulit Batang Mahoni (Swietenia mahagoni) - Mashuri Saputra; Utami Sri Hastuti; Abdul Gofur (Bioscientist : Jurnal Ilmiah Biologi, 2020)
The purpose of this study was to develop a handout based on the results of research on the antibacterial power of mahogany leaf and bark extract (Swietenia mahagoni). This research is a development research which refers to the ADDIE development model which consists of five stages, namely analyzing, designing, developing, implementing, and evaluating. The research object was students of the Biology Education Study Program, FSTT, Mandalika University of Education who had taken the Microbiology course. Handouts were validated by material expert validators, media experts, and a readability test to assess the practicality of handouts was carried out by students of the Biology Education Study Program, FSTT, Mandalika University of Education. The data were collected through a questionnaire and analyzed qualitatively and quantitatively. The percentage of results from the validation of experts in microbiology material was 97.61%, the validation of the instructional media experts was 97.72%, and the readability test by students was 91.79%. The results showed that handouts based on the results of research on the antibacterial power of mahogany leaf and bark extracts were very valid and suitable for use as teaching materials.